Printculture of Surgical Pathology and Autopsy Specimens: A Comparison to Standard Culture Techniques. Issue 6 (23rd July 2019) - McMullen, Phillip D; Tesic, Vera; Pytel, Peter
Abstract: Objectives: Printculture is a method of microbiologic assessment previously described for use in the autopsy setting. We sought to compare printculture of surgical and autopsy pathology specimens to standard microbiology culture using matrix-assisted laser desorption/ionization–time of flight (MALDI-TOF)–based colony identification. Methods: Printculture was performed on 18 frozen samples with corresponding standard culture results. The results of MALDI-TOF identification of colonies recovered by printculture were compared with standard cultures, and percent concordance was calculated. Results: There was 95.8% concordance to standard culture methods for cases with infections and 100% concordance for cases without infection. The pattern of growth was found to aid in the distinction between contamination and true infection. Conclusions: Printculture allows the identification of microorganisms from routinely frozen tissues and provides a bridge between microbiology and histomorphology through the identification of associated histologic features of infection. This technique can be successfully integrated into autopsy and surgical pathology workup of potentially infected tissues.